Food systems and the political economy: A lens for understanding farmer-herder conflicts - Flintan, Fiona; Nassef, Magda; Domingo, Pilar (2023)
Conflict between farmers and livestock herders, normally pastoralists, has received heightened attention over the last two decades. However, primary research on the causes of these conflicts is scarce. Farming and pastoralism are two food production systems that are increasingly clashing as pressure for land rises in a context of poor tenure security and land use planning and development narratives that prioritize crop farming over livestock production despite a steadily growing demand for livestock products.This brief outlines a preliminary research framework developed by the CGIAR Research Initiative on Fragility, Conflict and Migration and the project Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC).